Prediction on large scale data using extreme gradient boosting - Sawon, Md.Tariq Hasan; Hosen, Md. Shazzed (BRAC University, 2016)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2016.